Navigating Moral Cleansing: the Role of the 'Macbeth Effect' in Decision-Making Among Leaders of Private Nursing Schools - Imelda Ingir Ladjar; Warjiman Warjiman; Maria Frani Ayu Andari Dias; Mohammad Basit (Indonesian Journal of Global Health Research, 2024)
Private nursing schools in South Kalimantan face increasing pressure to produce high-quality, ethically driven nursing professionals, aligning with Indonesia’s “Golden Vision 2045.” Within this context, the "Macbeth effect"—a psychological phenomenon where individuals experience guilt, anxiety, or a compulsion to "cleanse" themselves after confronting morally ambiguous situations—poses a challenge to ethical leadership. This study investigates the manifestation of the "Macbeth Effect"—the compulsion to morally cleanse oneself following ethically ambiguous situations—among leaders of private nursing schools in South Kalimantan, Indonesia. Using a qualitative case study approach, in-depth interviews were conducted with five school leaders to capture their experiences and perceptions of moral responsibility and ethical decision-making. Thematic analysis was employed to identify key themes, focusing on how the Macbeth Effect shapes leadership behavior, decision-making processes, and organizational dynamics within nursing education institutions. Findings reveal that leaders frequently exhibit moral cleansing behaviors, such as self-evaluation, transparency in decision-making, and using mediators to handle conflicts. While the Macbeth Effect enhances ethical leadership practices, it also introduces challenges that may impact mental well-being and leadership efficacy. Practical strategies, including promoting a culture of transparency, emotional support, and task delegation, are recommended to mitigate the psychological burden associated with moral cleansing. This research contributes to understanding ethical leadership in nursing education and highlights the need for support systems to sustain leaders’ mental resilience and ethical commitment.